2018
DOI: 10.1080/08985626.2018.1500645
|View full text |Cite
|
Sign up to set email alerts
|

‘And now I’m free’: Women’s empowerment and emancipation through entrepreneurship in Saudi Arabia and Sweden

Abstract: Critical perspectives have called for the study of women's entrepreneurship as a route to social change. This 'social turn' claims women are empowered and/or emancipated through entrepreneurship with limited problematisation of how these interchangeably used concepts operate. Using an institutional perspective in combination with a narrative approach, we investigate women entrepreneurs' life stories on their 'road to freedom' where entrepreneurial activity enables them to 'break free' from particular gendered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 90 publications
2
101
0
14
Order By: Relevance
“…in Fieldsand [5], women farmers tend to reject the claim that they are over-burdened because of their attachment to the traditional agricultural lifestyle and their wish to preserve the traditional farming system. This is confirmed by Alkhaled and Berglund [47], who showed that although women empower themselves, they are not emancipated; they act within their cultural system and sustain the family farm through the fulfilment of multiple tasks.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…in Fieldsand [5], women farmers tend to reject the claim that they are over-burdened because of their attachment to the traditional agricultural lifestyle and their wish to preserve the traditional farming system. This is confirmed by Alkhaled and Berglund [47], who showed that although women empower themselves, they are not emancipated; they act within their cultural system and sustain the family farm through the fulfilment of multiple tasks.…”
Section: Discussionmentioning
confidence: 75%
“…These structures refer, for example, as mentioned in the state of the art on gender roles in agriculture, to the allocation of resources (land). According to Alkhaled & Berglund [47], empowerment is distinguished from emancipation, because it does not challenge the pervasive patriarchal order. This means that through social farming, women acquire autonomy, professionalization, and self-realization opportunities, but in certain contexts, they still act within the patriarchal system.…”
Section: Social Entrepreneurship In Agriculture For Women Empowermentmentioning
confidence: 99%
“…However, in situations of poverty and isolation, it is difficult to start with entrepreneurial activities (Scott et al, 2012). These studies also show that entrepreneurship as a social change includes both the experience of suppression and empowerment, leading to emancipation (Alkhaled & Berglund, 2018;Calás et al, 2009).…”
Section: Other Related Conceptsmentioning
confidence: 84%
“…Critical studies on entrepreneurship have also emerged, exploring entrepreneurship as a social change, especially in the area of female entrepreneurship (Calás et al, 2009). Entrepreneurship for women is a means to overcome obstacles, to feel empowered in male-dominated power structures and to feel emancipated to take actions towards change (Alkhaled & Berglund, 2018). However, in situations of poverty and isolation, it is difficult to start with entrepreneurial activities (Scott et al, 2012).…”
Section: Other Related Conceptsmentioning
confidence: 99%
“…According to Schumpeter, one of capitalism's cardinal virtues is its ability to provide the economic and moral premises for entrepreneurs to transgress the social class system (Schumpeter, 1955a). In this vein, entrepreneuring has been perceived as a transformative socioeconomic practice, potentially pulling its subjects toward a better life (Alkhaled & Berglund, 2018;Tobias et al, 2013). The second is the entrepreneurial emancipation to inflict changes in society in a broader sense, a "positive" (Berlin, 1969) conception of emancipation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%